STUDENTS’ PERSONAL INTEREST TOWARDS PROJECT – BASED LEARNING - Rosales, Jeffry Juan; Sulaiman, Fauziah (PEOPLE: International Journal of Social Sciences, 2016)
This study was attempted by the researcher to examine students’ personal interest with the implementation of Project-Based Learning (PBL) – egg drop project towards learning physics in three (3) different perspectives which were overall students, gender (i.e., male and female students) and location (i.e., urban and rural students). Students have done egg drop project to have better understanding towards physics concepts (i.e., momentum, impulse and impulsive force).This research was taken place in one selected school at Tuaran (i.e., 20 urban students) and Kota Marudu (i.e., 18 rural students) Districts and was carried out by thirty-eight (38) Form Four students (i.e., 17 male and 21 female students) for both schools in total. Quantitative data were collected via The Colorado Learning Attitude about Science Survey (CLASS) – personal interest category before and after PBL. Gathered data were analysed by using Statistical Package for Social Science Version 20.0 for windows (SPSS) to compare students’ pre-survey and post-survey responses by using Wilcoxon Signed Ranks Tests and Paired Samples-t-test. Wilcoxon Signed Ranks Tests results showed that students’ personal interest in each perspective have a statistically significant difference after PBL except rural students’ personal interest have no significant difference after PBL. Paired samples-t-test results showed that students’ personal interest in each perspective have a statistically significant difference after PBL. Through PBL, students’ personal interest have increased and able to change students’ perception towards learning physics.